1001 Inventions & Awesome Facts from Muslim Civilization - Published by National Geographic (Washinton D.C National Geographic, 2012)
We often think that people from a thousand years ago were living in the Dark Ages. But from the 7th century onward in Muslim civilization there were amazing advances and inventions that still influence our everyday lives. People living in the Muslim world saw what the Egyptians, Chinese, Indians, Greek, and Romans had discovered and spent the next one thousand years adding new developments and ideas. Inventors created marvels like the elephant water clock, explorers drew detailed maps of the world, women made scientific breakthroughs and founded universities, architects built huge domes larger than anywhere else on earth, astronomers mapped the stars and so much more! This book takes the formula of facts, photos, and fun, and applies it to this companion book to the 1001 Inventions exhibit from the Foundation for Science, Technology, and Civilization. Each page is packed with information on this little-known history, but also shows how it still applies to our world today.
Include Color Illustrations, Resources and Index
Keywords: Technological innovations